Transcultural adaptation and new proposal for the nursing outcome, Physical condition (2004) - Jessica Rojas Navarrete; Paloma Echevarría Pérez; César Leal Costa (Universidade de São Paulo, 2018)
ABSTRACT Objectives: cross-culturally adapt to the Spanish context and make a new proposal for the nursing outcome, Physical Condition (2004), of the Nursing Outcomes Classification (NOC) for its precise use in clinical practice. Method: a cross-cultural adaptation study and a proposal for the nursing outcome, Physical Condition, was conducted and supported by the opinion of 26 experts. The data was obtained through an electronic form, and a quantitative analysis was conducted, using the SPSS software. Results: the version adapted to the Spanish context was obtained and the proposal of the outcome, Physical Condition, received agreement from 26 experts, with a mean score greater than 7.6 for adequacy of the outcome definition and its indicators, and 8.5 for the relevance of the indicators. Conclusions: the version adapted to the Spanish context and a new proposal for Physical Condition were obtained. The results obtained indicate a high level of adequacy and relevance, an instrument of great utility in the clinic, and research was obtained to evaluate the interventions directed to the improvement of the physical condition.